Nuclear interferon-inducible protein 16 promotes silencing of herpesviral and transfected DNA - Orzalli, Megan H. (National Academy of Sciences, 2013)
Mammalian cells have evolved mechanisms to silence foreign DNA introduced by viruses or by transfection. Upon herpesviral infection of cells, the viral genome is chromatinized in an attempt by the host cell to restrict expression of the viral genome. HSV ICP0 acts to counter host-intrinsic and innate responses to viral infection. We have found that nuclear interferon (IFN)-inducible protein 16 (IFI16) acts as a restriction factor against ICP0-null herpes simplex virus 1 (HSV-1) to limit viral replication and immediate–early gene expression. IFI16 promoted the addition of heterochromatin marks and the reduction of euchromatin marks on viral chromatin. IFI16 also restricted the expression of plasmid DNAs introduced by transfection but did not restrict SV40 DNA introduced into the cellular nucleus in the form of nucleosomal chromatin by viral infection. These results argue that IFI16 restricts unchromatinized DNA when it enters the cell nucleus by promoting the loading of nucleosomes and the addition of heterochromatin marks. Furthermore, these results indicate that IFI16 provides a broad surveillance role against viral and transfected DNA by promoting restriction of gene expression from the exogenous DNA and inducing innate immune responses.